Scientific production on diversity and inclusion management: a mapping of LGBTQIAPN+ research in the field of business (Emancipação, 2025)
This study aimed to carry out a systematic and integrative review of Brazilian scientific production on the LGBTQIAPN+ community, using the SPELL database. A total of 24 articles were identified and categorized into thematic areas such as tourism, marketing, public administration, organizational management, human resources, and culture. The resultsshow a predominance of theoretical and qualitative studies, with authors and institutions mainly concentrated in the South and Central-West regions of Brazil. The findings also reveal that research tends to focus primarily on the categories of Lesbians, Gays, Bisexuals, and Trans/Travestis, while other identities included in the LGBTQIAPN+ acronym remain underexplored. Based on the analysis, the study outlines trends, gaps, and research directions for advancing the field of diversity management.
Keywords: Studies Organizations; Diversity Management; LGBTQIAPN